Blood-CNS Barrier Impairment in ALS patients versus an animal model - Garbuzova-Davis, Svitlana; Sanberg, Paul R. (Frontiers in Cellular Neuroscience, 2014)
Amyotrophic lateral sclerosis (ALS) is a severe neurodegenerative disease with a compli-cated and poorly understood pathogenesis. Recently, alterations in the blood-Central Nervous System barrier (B-CNS-B) have been recognized as a key factor possibly aggravating motor neuron damage. The majority of findings on ALS microvascular pathology have been deter-mined in mutant SOD1 rodent models, identifying barrier damage during disease develop-ment which might similarly occur in familial ALS patients carrying the SOD1 mutation. However, our knowledge of B-CNS-B competence in sporadic ALS (SALS) has been limited. We recently showed structural and functional impairment in postmortem gray and white mat-ter microvessels of medulla and spinal cord tissue from SALS patients, suggesting pervasive barrier damage. Although numerous signs of barrier impairment (endothelial cell degenera-tion, capillary leakage, perivascular edema, downregulation of tight junction proteins, and microhemorrhages) are indicated in both mutant SOD1 animal models of ALS and SALS pa-tients, other pathogenic barrier alterations have as yet only been identified in SALS patients. Pericyte degeneration, perivascular collagen IV expansion, and white matter capillary abnor-malities in SALS patients are significant barrier related pathologies yet to be noted in ALS SOD1 animal models. In the current review, these important differences in blood-CNS barrier damage between ALS patients and animal models, which may signify altered barrier transport mechanisms, are discussed. Understanding discrepancies in barrier condition between ALS patients and animal models may be crucial for developing effective therapies.